Systems engineering handbook : a guide for system life cycle processes and activities - Walden, David D.; Roedler, Garry J.; Forsberg, Kevin; Hamelin, R. Douglas; Shortell, Thomas M. (Wiley, 2015)
A detailed and thorough reference on the discipline and practice of systems engineering The objective of the International Council on Systems Engineering (INCOSE) Systems Engineering Handbook is to describe key process activities performed by systems engineers and other engineering professionals throughout the life cycle of a system. The book covers a wide range of fundamental system concepts that broaden the thinking of the systems engineering practitioner, such as system thinking, system science, life cycle management, specialty engineering, system of systems, and agile and iterative method.
Keywords: Systems engineering -- Handbooks, manuals, etc.; Product life cycle -- Handbooks, manuals, etc.; elektronické knihy; electronic books